Rancang Bangun Sistem Informasi Akademik Mahasiswa Berbasis Website - Misdiyanto Misdiyanto; Ahmad Fadli Muhaimin Nourdy; Ira Aprilia (INTEGER: Journal of Information Technology, 2026)
This study aims to design and develop a web-based academic information system at Universitas Panca Marga Probolinggo to facilitate the management of student academic data. The research method used is the waterfall model software development methodology, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. The results of this study indicate that the developed academic information system can improve efficiency and accuracy in managing academic data, as well as make it easier for students and lecturers to access academic information.Keywords : academic information system, website, Panca Marga University.